Isolation and structure elucidation of anti-infective agent(s) from lunasia amara blanco - Salvador, Lilibeth Apo (Quezon City College of Science, University of the Philippines, 2006)
The endemic Philippine plant Lunasia amara blanco was screened for anti-infective activity against the true pathogen Mycobacterium tuberculosis, opportunistic pathogen Mycobacterium phlei, and dermatophytic fungus trichophyton mentagrophytes. The crude extract showed broad spectrum anti-infective activity, inhibiting the growth of all three organisms. A bioactivity-directed purification of the anti-infective agents from L. amara Blanco was done. The hexane extract yielded one new natural compound, 4,6-dimethoxy-2-phenylquinoline (C17H15NO2), with broad spectrum anti-infective activity. It had a minimum inhibitory concentration of 12.18μg/mL against M. tuberculosis determined by microplate alamar blue assay (MABA) and antimicrobial index of 1.0 and 1.6 against M. phei and T. mentagrophytes respectively determined from agar cup diffusion assay. Cytotoxicity testing on this isolate showed that it has moderate cytotoxicity towards normal cells with IC50 of 28.30 μg/mL, which may contribute to its broad anti-infective activity. The ethyl acetate extract yielded one new compound 7-methoxygraveolinine (C18H15NO4) and one known quinolone alkaloid edulein (C17H15NO2), with specific activity against T. mentagrophytes and M. phlei respectively. 7-methoxygraveolinine exhibited an antimicrobial index of 2.8 against T.mentagrophytes, comparable to the standard drug fluconazole while exhibiting no significant cytotoxicity to normal cells. It is desirable that drugs which inhibit the growth of dermatophytic fungus be non-cytotoxic to normal cells to minimize side effects. The non-cytotoxicity of 7-methoxygraveolinine towards normal cells and its comparable bioactivity to the standard drug fluconazole in inhibiting T.mentagrophytes makes quinoline alkaloids promising leads for new antifungal drugs. Edulein showed weak activity against M. phlei, with antimicrobial index of 0.5, and was non-cytotoxic to normal cells.
Thesis (M.S. Chemistry)--University of the Philippines Diliman
Keywords: Medicinal plants -- Philippines; Herbs -- Therapeutic use -- Philippines